The Zero-Grid Instagram Trend Among Gen Z in Pekanbaru - Risa Amalia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The Grid Zero trend on Instagram has become an intriguing phenomenon among Gen Z, including in Pekanbaru, Riau. This generation, born between 1997–2012, grew up alongside the rapid rise of social media, making Instagram their primary platform for self-expression. Grid Zero initially referred to a minimalist aesthetic concept with a neat and consistent feed, but it has now evolved to encompass how Gen Z manages their digital presence. This study employs a qualitative method with a phenomenological approach, involving several Gen Z individuals in Pekanbaru through in-depth interviews, observation, and documentation, with data validation carried out via triangulation and prolonged engagement. The findings reveal that Gen Z in Pekanbaru chooses Grid Zero primarily to protect their privacy, ensuring their personal lives are not easily accessible to the public, especially considering the strong local social norms. The pressure of Instagram’s aesthetic standards also makes them more comfortable not posting at all rather than worrying about being judged. The fear of being compared within closely connected social circles further influences this choice, as does their rejection of an image-centric culture that demands perfection. They prefer more temporary platforms like Stories or TikTok to express themselves without leaving a permanent trace. For some, an empty feed is even perceived as cool, mysterious, and exclusive. These findings highlight that Grid Zero is not merely an aesthetic trend, but a strategy employed by Pekanbaru’s Gen Z to cope with social pressure, protect their mental health, and maintain a more authentic self-image in the digital era.